Transport Infrastructures and Acceptability: the Role of Economic Evaluation for Conflict Mitigation - Silvia Maffii; Riccardo Parolin (TeMA, 2011)
Large and medium-size transport infrastructure shall increasingly cope with acceptability-related problems. This is due to the lack of confidence that nowadays characterises the relations between public administrations and their citizens, as well as between citizens and the project promoters. Moreover, the subjects that take advantage from the project implementation and those not often do not coincide, whereas the latter are not compensated for the damages they bear. A sound cost-benefit analysis supporting the entire decision-making process may be a valuable tool for fostering the dialogue with all concerned subjects, provided that a set of basic conditions is met. Firstly, cost-benefit analysis has to be credible as far as the effects generated by the project are concerned. Therefore, it shall: (i) secure transparency of: results achieved by the evaluation (including the assumptions and criteria that led to such results), and procedures embedded into the evaluation process; (ii) be performed by independent evaluators rather than those sponsoring the project; (iii) be as much robust as possible, and finally (iv) deliver structured and thorough risk analyses. In order to reinforce credibility and soundness of the analysis and the evaluations undertaken, previous project experiences shall be duly taken into account, which implies fine-tuning ex-ante evaluations upon the basis of the results obtained by ex-post analysis of projects already implemented. Additionally, the evaluation shall be dynamic, as it shall back since the very beginning the whole process of infrastructure designing, and until the project is finalised. Transparency of such process is then a key pre-requisite . The second condition refers to the fact that stakeholders interested into the project shall be actively involved into the planning process. Further major token is that the economic evaluation at the level of approximation featuring the various steps of the project cycle feeds and frame the public debate on the project implementation. This article is based upon results from research activities, enriched with the explanation of few recent case-studies.